2006
DOI: 10.2105/ajph.2004.041806
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of Patients’ Social and Behavioral Characteristics and Race Disparities in Treatment Recommendations for Men With Coronary Artery Disease

Abstract: Our findings point to the importance of research and intervention strategies addressing the ways in which providers' beliefs about patients mediate disparities in treatment. In addition, they highlight the need for discourse and consensus development on the role of social factors in clinical decisionmaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
149
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 70 publications
3
149
0
2
Order By: Relevance
“…This finding is consistent with a growing body of evidence indicating that how a physician perceives a patient (likeable, intelligent, adherent) is related to how that doctor treats the patient (Amir, 1987;Beach, Roter, Wang, Duggan & Cooper, 2006a;Gerbert, 1984;Hall et al, 1993;Hall et al, 2002;Van Ryn et al, 2006). However, to assume a causal pathway from perception to communication would be premature.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding is consistent with a growing body of evidence indicating that how a physician perceives a patient (likeable, intelligent, adherent) is related to how that doctor treats the patient (Amir, 1987;Beach, Roter, Wang, Duggan & Cooper, 2006a;Gerbert, 1984;Hall et al, 1993;Hall et al, 2002;Van Ryn et al, 2006). However, to assume a causal pathway from perception to communication would be premature.…”
Section: Discussionsupporting
confidence: 84%
“…Second, variability in physicians' communication and perceptions may be related to the patients' demographic characteristics. Even the most well-meaning and egalitarian physicians may have stereotypes or biases based on a patient's demographic status (Burgess, Fu & Van Ryn, 2004;Van Ryn, Burgess, Malat & Griffin, 2006). Racial bias, in particular, has been implicated in research showing that some physicians associate more negative attributes (e.g., non-compliant, less intelligent, more likely to abuse drugs and alcohol) to minority and less educated patients (Van Ryn & Burke, 2000), perceptions that in turn may affect physicians' informativeness (Amir, 1987) and medical decision-making (Krupat, Irish, Kasten, Freund, Burns, Moskowitz et al 1999;Schulman, Berlin, Harless, Kerner, Sistrunk, Gersh et al 1999).…”
Section: Conceptual Framework: An Ecological Approachmentioning
confidence: 99%
“…While studies have suggested that provider recommendations for a variety of medical or surgical procedures vary by patient race/ethnicity, it is unclear to what degree these variations are based on clinical rather than nonclinical factors, including racial stereotypes. 26,[40][41][42][43] In our prior qualitative study, AA and white women who underwent sterilization reported that their provider did not, in fact, influence their decision making about sterilization. 9 In summary, in this nationally representative sample of women of reproductive age, we found that higher rates of unintended and unwanted pregnancies may help explain why minority women are more likely to undergo tubal sterilization compared to white women.…”
Section: Discussionmentioning
confidence: 95%
“…9,10 These studies have typically presented physicians with clinical vignettes 11,12 or used observational databases and adjusted for confounding factors. 13 Far fewer studies have focused on discrimination on the basis of patient socioeconomic status. 8,14 Audit studies, a well-established method of testing for discrimination in labour and housing markets, [15][16][17] have been used in the United States to show that Medicaid recipients and patients who are uninsured encounter substantial barriers to care.…”
Section: Discussionmentioning
confidence: 99%